Late-Onset Bartter Syndrome Type II Due to a Novel Compound Heterozygous Mutation in KCNJ1 Gene: A Case Report and Literature Review - Tian, Mi; Peng, Hui; Bi, Xin; Wang, Yan-Qiu; Zhang, Yong-Zhe; Wu, Yan; Zhang, Bei-Ru (Frontiers in Medicine, 2022)
Background Bartter syndrome (BS) type II is a rare autosomal recessive renal tubular disorder caused by mutations in the KCNJ1 gene, which encodes the apical renal outer medullary potassium (ROMK) channel in the thick ascending limb (TAL) of Henle’s loop. BS type II is typically considered as a disorder of infancy and seldom seen in adults. Case Presentation A 34-year-old woman was admitted with generalized body numbness and hand convulsions, without growth retardation. Laboratory tests revealed hypokalemic metabolic alkalosis, hyperreninemic hyperaldosteronism, and nephrocalcinosis. She was misdiagnosed during the initial diagnosis process and was finally diagnosed with late-onset BS type II via genetic testing through next-generation sequencing combined with Sanger sequencing. A novel compound heterozygous p.Leu207Ile/p. Cys308Arg variant in exon 5 of the KCNJ1 gene from her parents was identified and speculated to be a potential pathogenic gene variation. Conclusion We report a case of late-onset BS type II with a novel compound heterozygous mutation in KCNJ1. Both variants are novel and have never been reported. Our report will have a significant impact on the diagnosis of BS in other patients without typical clinical presentations and emphasizes the importance of genetic investigation.